2015
DOI: 10.1007/s11998-015-9695-y
|View full text |Cite
|
Sign up to set email alerts
|

Scratch- and wear-resistant photoluminescent silicone epoxy coatings on floor tiles

Abstract: Photoluminescent silicone epoxy resins were prepared by physical dispersion of SrAl2O4:Eu2+, Dy3+ pigments. The resin was deposited on ceramic tiles for flooring by automatic drawdown and left to harden at ambient conditions. Morphology of the coated tiles was measured by contact gage profilometry and field emission gun scanning electron microscopy. Mechanical response was investigated by pencil and cross-hatch scratch tests; depth-sensing indentation measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, it has been shown that metal oxide nanoparticles such as ZnO and TiO 2 can significantly improve the resistance of coatings and prevent the degradation of paint. [5][6][7] Polyaniline (PA) is one of the most promising conducting polymers, which is widely used for corrosion protection purposes, due to low cost, easy preparation, and good environmental stability. [8][9][10][11][12][13] In recent years, several studies have been carried out to enhance the properties of PA for better corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that metal oxide nanoparticles such as ZnO and TiO 2 can significantly improve the resistance of coatings and prevent the degradation of paint. [5][6][7] Polyaniline (PA) is one of the most promising conducting polymers, which is widely used for corrosion protection purposes, due to low cost, easy preparation, and good environmental stability. [8][9][10][11][12][13] In recent years, several studies have been carried out to enhance the properties of PA for better corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, as a two‐dimensional sheet of carbon, has being widely studied across a number of areas due to its exceptional micromechanical and thermal properties . Recently, considerable amount of papers have reported that the graphene/polymer composite possesses enhanced barrier properties that are beneficial for high anticorrosion performances . Unlike carbon nanotubes that can only provide similar mechanical benefits, these lightweight sheets can reduce oxygen permeability of host membranes .…”
Section: Introductionmentioning
confidence: 99%
“…The photocuring of epoxy resins [1][2][3][4][5][6] has been extensively studied due to the wide applicability, such as negative-type photoresists, coating materials and printing materials, to overcome the oxygen inhibition of the photocuring system using acrylates [1]. We are strongly interested in UV light-emitting diodes (UV LEDs) as the light sources for UVcuring technologies due to their long life, high stability, bright output, compactness, and low power requirement.…”
Section: Introductionmentioning
confidence: 99%